A correlational study between perceived parenting style, psychological well-being, and emotional intelligence among adolescents - Priyanka Yadav (Wolters Kluwer Medknow Publications, 2021)
Background: In many reviews, it is found that parental responsiveness, parental emotion-related coaching, and parental positive demandingness are related to children's higher emotional intelligence (EI), while parental negative demandingness is related to children's lower EI. There is a lack of Indian work in this area. Aim: To study the role of EI and parenting style in predicting psychological well-being among adolescents in an Indian scenario. Materials and Methods: This cross-sectional, analytical study was carried out on 75 boys and 75 girls in the age range of 15–18 years and attending school. They were assessed with the sociodemographic data sheet, trait EI questionnaire, psychological well-being inventory, and parental authority questionnaire. After the administration on different scales, the scoring was done and data were analyzed with SPSS. Results: There were no gender differences in the scores of EI, psychological well-being, and self-reported parenting style scores. There was a significant positive co-relation between well being and authoritative, authoritarian and autonomy, positive relationship. and self acceptance. Authoritarian parenting style is highly correlated with EI in comparison to authoritative and permissive parenting styles. Conclusion: Authoritarian parenting style is most suitable for the development of EI and on the other hand, permissive parenting style has the least role in the development of EI. EI and parenting style are found to predict the psychological well-being in adolescents.